Dr. Sreenath Sukumaran and Shafiqah receive UMP Postgraduate Research Prize - Norhidayah, Mohamad (2022)
PAYA BESAR, 5 November 2022 – Dr. Sreenath Sukumaran, 29 and Shafiqah Hanis Mohd Fauzi, 26, were overjoyed to receive the UMP Postgraduate Research Award at the recent Universiti Malaysia Pahang (UMP) 17th Convocation Ceremony.